Impact of neutron-induced displacement damage on the single event latchup sensitivity of bulk CMOS SRAM - 潘霄宇 郭红霞 罗尹虹 张凤祁 丁李利 魏佳男 赵雯 (Chinese physics B, 2017)
Since the displacement damage induced by the neutron irradiation prior has negligible impact on the performance of the bulk CMOS SRAM, we use the neutron irradiation to degrade the minority carrier lifetime in the regions responsible for latchup. With the experimental results, we discuss the impact of the neutron-induced displacement damage on the SEL sensitivity and qualitative analyze the effectiveness of this suppression approach with TCAD simulation.